Aggregation‐Induced Phosphorescent Imaging in the Second Near‐Infrared Window. Issue 24 (7th October 2021) - Chang, Baisong; Zhu, Hao; Wu, Yifan; Wu, Shaolong; Zhang, Liqin; Qu, Chunrong; Ren, Ying; Cheng, Zhen
Abstract: The fluorescence imaging in the second near‐infrared window (NIR‐II, 1000–1700 nm) is a very promising and actively studied technique, whereas optical imaging via NIR‐II phosphorescence has been seldom studied. Here, an aggregation‐induced selective signal activation strategy is reported, which relies on switching of radiative mode of probe from weak fluorescence to strong NIR‐II phosphorescence. Copper indium selenium (Cu‐In‐Se) quantum dots emit extremely weak fluorescence in isolated state, while their aggregation remarkably lights NIR‐II phosphorescence up at ≈ 1045 nm with over 2.7 × 10 3 ‐fold increase in luminescent lifetime. Aggregation‐induced emission‐mode‐switching has been confirmed by encapsulating Cu‐In‐Se assembles with mesoporous silica nanoparticles (Cu‐In‐Se@MSN), displaying unique phosphorescence‐type emission. NIR‐II phosphorescence signals enable Cu‐In‐Se@MSN to exhibit impressive lifetime imaging and high‐order branches of vessels can be accurately determined. Studies on the origin of radiative‐mode‐switching not only provide a new insight into photophysical process, but also may lay groundwork for designing smart NIR‐II probes. Abstract : NIR‐II (near‐infrared) phosphorescent imaging has been developed in this work, which relies on radiative mode switching strategy from negligible fluorescence to bright NIR‐II phosphorescence. As a long‐lived NIR‐II phosphorescent probe, Cu‐In‐Se quantum dots hold great potential for in vivo imaging of small and high‐order branches of vessels, owing to their long lifetime, large Stokes shift, and autofluorescence‐free photophysical properties.